Quality of life in patients with Parkinson's disease: Translation and psychometric evaluation of the Iranian version of PDQ-39. - Nojomi, M; Mostafavian, Z; Shahidi, G; Jenkinson, C (2010)
BACKGROUND: Health related quality of life is an important outcome measure in studies involving patients with chronic neurological conditions. Disease specific patient reported outcome measures (PROMs) are increasingly used as primary end points in clinical trials. The most widely used disease specific PROM is the 39 item Parkinson's Disease Questionnaire (PDQ-39). The aim of this study was to determine validity and reliability of Persian PDQ-39. METHODS: Two hundred Parkinson's disease patients attending neurologic clinics of teaching hospitals were recruited. PD patients completed a translated version of the PDQ-39. Internal consistency reliability of the questionnaire was assessed by Cronbach's alpha coefficient. Reproducibility was assessed across the 3-week interval using the intraclass correlation coefficient. To assess convergent validity, results on the PDQ-39 were correlated with those gained on the SF-36. Discriminate validity of questionnaire was assessed by comparing PDQ-39 scores and the severity and the duration of disease. RESULTS: A value of 0.93 (Cronbach's α) was gained for the summary score (PDQ-SI), indicating high levels of internal reliability. Alpha value of seven domains was greater than 0.70. The intraclass correlation coefficient ranged from 0.47 to 0.90. The range of correlation coefficients between domains of SF-36 and PDQ-SI was from -0.40 to -0.61. There was a statistically significant difference between severity of disease and mean scores of PDSI. CONCLUSIONS: This study provides evidence that the Persian version of PDQ-39 is a valid and reliable measure of quality of life in PD.